Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To verify that [tex]\((AB)^{-1} = B^{-1}A^{-1}\)[/tex] for the given matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex], we will take the following steps:
1. Define the matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ A = \begin{pmatrix} 3 & 2 \\ 7 & 5 \end{pmatrix} \][/tex]
[tex]\[ B = \begin{pmatrix} -2 & 7 \\ -3 & 9 \end{pmatrix} \][/tex]
2. Find the inverse of matrix [tex]\(A\)[/tex]:
Recall that for a 2x2 matrix [tex]\( \begin{pmatrix} a & b \\ c & d \end{pmatrix} \)[/tex], the inverse is given by:
[tex]\[ A^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For matrix [tex]\(A\)[/tex]:
[tex]\[ A = \begin{pmatrix} 3 & 2 \\ 7 & 5 \end{pmatrix} \][/tex]
The determinant of [tex]\(A\)[/tex] is:
[tex]\[ \text{det}(A) = 3 \cdot 5 - 2 \cdot 7 = 15 - 14 = 1 \][/tex]
Hence, the inverse of [tex]\(A\)[/tex] is:
[tex]\[ A^{-1} = \begin{pmatrix} 5 & -2 \\ -7 & 3 \end{pmatrix} \][/tex]
3. Find the inverse of matrix [tex]\(B\)[/tex]:
Similarly, for matrix [tex]\(B\)[/tex]:
[tex]\[ B = \begin{pmatrix} -2 & 7 \\ -3 & 9 \end{pmatrix} \][/tex]
The determinant of [tex]\(B\)[/tex] is:
[tex]\[ \text{det}(B) = (-2) \cdot 9 - 7 \cdot (-3) = -18 + 21 = 3 \][/tex]
Hence, the inverse of [tex]\(B\)[/tex] is:
[tex]\[ B^{-1} = \frac{1}{3} \begin{pmatrix} 9 & -7 \\ 3 & -2 \end{pmatrix} = \begin{pmatrix} 3 & -2.33333333 \\ 1 & -0.66666667 \end{pmatrix} \][/tex]
4. Calculate the product [tex]\(AB\)[/tex]:
[tex]\[ AB = \begin{pmatrix} 3 & 2 \\ 7 & 5 \end{pmatrix} \begin{pmatrix} -2 & 7 \\ -3 & 9 \end{pmatrix} \][/tex]
Compute each element of the resulting matrix:
[tex]\[ AB = \begin{pmatrix} 3 \cdot (-2) + 2 \cdot (-3) & 3 \cdot 7 + 2 \cdot 9 \\ 7 \cdot (-2) + 5 \cdot (-3) & 7 \cdot 7 + 5 \cdot 9 \end{pmatrix} = \begin{pmatrix} -6 - 6 & 21 + 18 \\ -14 - 15 & 49 + 45 \end{pmatrix} = \begin{pmatrix} -12 & 39 \\ -29 & 94 \end{pmatrix} \][/tex]
5. Find the inverse of matrix [tex]\(AB\)[/tex]:
The determinant of [tex]\(AB\)[/tex] is:
[tex]\[ \text{det}(AB) = (-12) \cdot 94 - 39 \cdot (-29) = -1128 + 1131 = 3 \][/tex]
Hence, the inverse of [tex]\(AB\)[/tex] is:
[tex]\[ (AB)^{-1} = \frac{1}{3} \begin{pmatrix} 94 & -39 \\ 29 & -12 \end{pmatrix} = \begin{pmatrix} 31.33333333 & -13 \\ 9.66666667 & -4 \end{pmatrix} \][/tex]
6. Compute the product [tex]\(B^{-1}A^{-1}\)[/tex]:
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 3 & -2.33333333 \\ 1 & -0.66666667 \end{pmatrix} \begin{pmatrix} 5 & -2 \\ -7 & 3 \end{pmatrix} \][/tex]
Compute each element of the resulting matrix:
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 3 \cdot 5 + (-2.33333333) \cdot (-7) & 3 \cdot (-2) + (-2.33333333) \cdot 3 \\ 1 \cdot 5 + (-0.66666667) \cdot (-7) & 1 \cdot (-2) + (-0.66666667) \cdot 3 \end{pmatrix} \][/tex]
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 15 + 16.33333331 & -6 - 7 \\ 5 + 4.66666669 & -2 - 2 \end{pmatrix} \][/tex]
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 31.33333333 & -13 \\ 9.66666667 & -4 \end{pmatrix} \][/tex]
7. Conclusion:
We observe that:
[tex]\[ (AB)^{-1} = B^{-1}A^{-1} = \begin{pmatrix} 31.33333333 & -13 \\ 9.66666667 & -4 \end{pmatrix} \][/tex]
This verifies that the relation [tex]\((AB)^{-1} = B^{-1}A^{-1}\)[/tex] holds true for the given matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex].
1. Define the matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ A = \begin{pmatrix} 3 & 2 \\ 7 & 5 \end{pmatrix} \][/tex]
[tex]\[ B = \begin{pmatrix} -2 & 7 \\ -3 & 9 \end{pmatrix} \][/tex]
2. Find the inverse of matrix [tex]\(A\)[/tex]:
Recall that for a 2x2 matrix [tex]\( \begin{pmatrix} a & b \\ c & d \end{pmatrix} \)[/tex], the inverse is given by:
[tex]\[ A^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For matrix [tex]\(A\)[/tex]:
[tex]\[ A = \begin{pmatrix} 3 & 2 \\ 7 & 5 \end{pmatrix} \][/tex]
The determinant of [tex]\(A\)[/tex] is:
[tex]\[ \text{det}(A) = 3 \cdot 5 - 2 \cdot 7 = 15 - 14 = 1 \][/tex]
Hence, the inverse of [tex]\(A\)[/tex] is:
[tex]\[ A^{-1} = \begin{pmatrix} 5 & -2 \\ -7 & 3 \end{pmatrix} \][/tex]
3. Find the inverse of matrix [tex]\(B\)[/tex]:
Similarly, for matrix [tex]\(B\)[/tex]:
[tex]\[ B = \begin{pmatrix} -2 & 7 \\ -3 & 9 \end{pmatrix} \][/tex]
The determinant of [tex]\(B\)[/tex] is:
[tex]\[ \text{det}(B) = (-2) \cdot 9 - 7 \cdot (-3) = -18 + 21 = 3 \][/tex]
Hence, the inverse of [tex]\(B\)[/tex] is:
[tex]\[ B^{-1} = \frac{1}{3} \begin{pmatrix} 9 & -7 \\ 3 & -2 \end{pmatrix} = \begin{pmatrix} 3 & -2.33333333 \\ 1 & -0.66666667 \end{pmatrix} \][/tex]
4. Calculate the product [tex]\(AB\)[/tex]:
[tex]\[ AB = \begin{pmatrix} 3 & 2 \\ 7 & 5 \end{pmatrix} \begin{pmatrix} -2 & 7 \\ -3 & 9 \end{pmatrix} \][/tex]
Compute each element of the resulting matrix:
[tex]\[ AB = \begin{pmatrix} 3 \cdot (-2) + 2 \cdot (-3) & 3 \cdot 7 + 2 \cdot 9 \\ 7 \cdot (-2) + 5 \cdot (-3) & 7 \cdot 7 + 5 \cdot 9 \end{pmatrix} = \begin{pmatrix} -6 - 6 & 21 + 18 \\ -14 - 15 & 49 + 45 \end{pmatrix} = \begin{pmatrix} -12 & 39 \\ -29 & 94 \end{pmatrix} \][/tex]
5. Find the inverse of matrix [tex]\(AB\)[/tex]:
The determinant of [tex]\(AB\)[/tex] is:
[tex]\[ \text{det}(AB) = (-12) \cdot 94 - 39 \cdot (-29) = -1128 + 1131 = 3 \][/tex]
Hence, the inverse of [tex]\(AB\)[/tex] is:
[tex]\[ (AB)^{-1} = \frac{1}{3} \begin{pmatrix} 94 & -39 \\ 29 & -12 \end{pmatrix} = \begin{pmatrix} 31.33333333 & -13 \\ 9.66666667 & -4 \end{pmatrix} \][/tex]
6. Compute the product [tex]\(B^{-1}A^{-1}\)[/tex]:
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 3 & -2.33333333 \\ 1 & -0.66666667 \end{pmatrix} \begin{pmatrix} 5 & -2 \\ -7 & 3 \end{pmatrix} \][/tex]
Compute each element of the resulting matrix:
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 3 \cdot 5 + (-2.33333333) \cdot (-7) & 3 \cdot (-2) + (-2.33333333) \cdot 3 \\ 1 \cdot 5 + (-0.66666667) \cdot (-7) & 1 \cdot (-2) + (-0.66666667) \cdot 3 \end{pmatrix} \][/tex]
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 15 + 16.33333331 & -6 - 7 \\ 5 + 4.66666669 & -2 - 2 \end{pmatrix} \][/tex]
[tex]\[ B^{-1}A^{-1} = \begin{pmatrix} 31.33333333 & -13 \\ 9.66666667 & -4 \end{pmatrix} \][/tex]
7. Conclusion:
We observe that:
[tex]\[ (AB)^{-1} = B^{-1}A^{-1} = \begin{pmatrix} 31.33333333 & -13 \\ 9.66666667 & -4 \end{pmatrix} \][/tex]
This verifies that the relation [tex]\((AB)^{-1} = B^{-1}A^{-1}\)[/tex] holds true for the given matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.